Physiological profiles of Australian surf boat rowers - Fell, J. W.; Gaffney, P. T. (Journal of Science and Medicine in Sport, 2001)
The physiological profiles of 17 open grade (OG) and 13 reserve grade (RG) male surfboat rowers (SBR) aged 19-44 years were determined and compared. Parameters investigated included anthropometry, agility, isometric strength, flexibility, rowing ergometer performance (MT), peak VO2 and arterialised blood pH, lactate and bicarbonate. Means were compared using t-tests. Multiple regression analyses provided a number of models for the prediction of MT performance in SBR. The mean age, height, mass, and sum of eight skinfolds for SBR are: 26.2 (+/-5.9) years, 180.5 (+/-6.0) cm, 84.4 (+/-9.3) kg and 78.2 (+/-26.2) mm respectively. OG rowers were significantly different from RG for the parameters of ergometer performance (OG: 1360.2+/-42.9 m; RG: 1316.4+/-41.8 m), peak ventilation (OG: 174.2+/-17.2 L x min(-1); RG: 154.8+/-22.1 L x min(-1)), and post exercise blood pH levels (OG: 6.98+/-0.07; RG: 7.04+/-0.07). Performance on a rowing ergometer successfully discriminates between OG and RG rowers with the best predictors of ergometer performance in SBR being height, peak ventilation, and post exercise pH.